AN ASSESSMENT OF PRESIDENT BUHARI ANTI-GRAFT CRUSADE 2015-2021 - Agah E. Benjamin; Ikenga A. Francis (Universitas PGRI Madiun, 2023)
The study examined President Muhammadu Buhari's anti-corruption initiative. The historical method was chosen because it entails a methodical analysis of secondary sources. Data analysis showed, among other things, that the administration of President Buhari's lacks a fundamental understanding of what drives corruption in Nigeria. The study finds that the fight against corruption seems to be more concentrated on punishing offenders than on addressing the socioeconomic factors that contribute to corruption. It is argued that the anti-corruption campaign was biased toward the prosecution of individuals from the Peoples Democratic Party, the former ruling party, who were viewed as opposition (PDP). The following recommendations are listed for this study based on the nature and character of President Buhari's Anti-Graft War and the conclusions drawn from. To combat corruption, social justice, equity, a reenergized socialization process, and a consistent rise in the standard of living of Nigerians particularly of civil servants and other public employees are required. The anti-graft organizations should also see to it that those who engage in corrupt behavior are swiftly prosecuted. There shouldn't be any holy cows, and there shouldn't be two sets of laws with different penalties for different groups of people. Audits of government organizations should be performed as needed. Almost no government agency conducts audits when they are required. Audit reports are routine and unimportant because they are not made public until three to four years after the incident. In addition, regardless of a person's ethnic background or political ties, there should be fairness and equity in the distribution of national resources, incomes, and the implementation of development projects and employment opportunities for all Nigerians. Nigeria needs leaders with a track record of moral rectitude, discipline, and dependability